Feasibility, Effectiveness and Safety of Elastomeric Pumps for Delivery of Antibiotics to Adult Hospital Inpatients-A Systematic Review - Joseph Spencer-Jones; Timothy Luxton; Stuart E. Bond; Jonathan Sandoe (MDPI AG, 2023)
Elastomeric infusion pumps (EMPs) have been implemented in many fields, including analgesia, chemotherapy and cardiology. Their application in antimicrobials is mainly limited to the outpatient setting, but with a need to optimise inpatient antimicrobial treatment, the use of EMPs presents a potential option. This review aimed to identify if the use of EMPs within an inpatient setting is feasible, effective and safe for antimicrobial use. Criteria for inclusion were human studies that involved the treatment of an infection with intravenous antimicrobial agents via an EMP. A search strategy was developed covering both the indexed and grey literature, with all study designs included. The review found 1 eligible study enrolling 6 patients. There was strong patient preference for EMPs (6/6), and daily tasks were easily completed whilst attached to the EMP. Nurses (5/5) also preffered the pumps, and the majority reported them as easy to use. The review has identified the need for further research in the area. Evidence for the use of EMPs to administer antibiotics in the inpatient setting is scarce, and more work is needed to understand the advantages to patients, to healthcare workers and from an antimicrobial stewardship perspective. Potential disadvantages that may put patients at risk also need investigating.